Strategy for Developing a Multicultural Islamic Religious Education Curriculum in Islamic Boarding School-Based Universities - Siti Robiatun; Hasan Yusuf; Tsani, Lulu Khoeru (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to analyze strategies for developing a multicultural Islamic Religious Education ( ) curriculum in pesantren-based universities to strengthen religious moderation and manage diversity. It employs a qualitative case study approach using interviews, observations, and documentation, with data analyzed through reduction, presentation, and conclusion drawing. Methodology: This study employed a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation, and documentation. The instruments included interview guidelines, observation sheets, and document analysis checklists. Informants were selected using purposive sampling. Data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. Main Findings: The results show that the multicultural curriculum is developed through integrating multicultural values into learning outcomes and curriculum structure, strengthening tolerance and inclusivity based on pesantren values, applying contextual and dialogical learning methods, and exemplifying religious moderation through kiai and lecturers, supported by a pesantren culture emphasizing ukhuwah, tasamuh, and ta’awun. Novelty/Originality of this study: This study offers a comprehensive model of multicultural Islamic Religious Education curriculum development in pesantren-based higher education by integrating planning, implementation, and evaluation stages. It highlights the role of pesantren culture as a foundational element in shaping inclusive, dialogical, and value-based learning, bridging Islamic teachings with multicultural competencies in a systematic and contextual framework.